Extractive Fermentation for Process integration and amplified pullulan production by A. pullulans in Aqueous Two Phase Systems - Badhwar, Parul (Sci Rep, 2019)
Extractive fermentation technique or in situ product recovery process is a novel technique to segregate the desired product simultaneously in a fermentation process. For economic and high yield production of pullulan, Extractive fermentation process was applied fermentation process of A. pullulans. Aqueous Two Phase system (ATPS) systems were designed with various molecular mass of PEG (400, 600, 4000 and 6000) and dextran or mono/bi-sodium phosphate salts. Systems with short Tie Line length (TLL) 6.7 and 7.5% w/w for PEG-Salt and PEG-dextran respectively were chosen. Volume ratio for all the systems was kept constant at 1.0 and pH 7.0 for PEG-dextran and PEG-NaH(2)PO(4) was maintained, whereas pH 9.0 was kept for PEG-Na(2)HPO(4). A. pullulans, was found to be viable with PEG-NaH(2)PO(4) and PEG-dextran systems. The biomass partitioned in the PEG rich top phase and the exopolysaccharide pullulan shown affinity towards the bottom phase. A maximum yield (36.47 g/L) was found with PEG 4000-Dextran 500 system of extractive fermentation process. The proposed process aptly integrates upstream and downstream process for continuous production and recovery of pullulan from the biomass, thus reducing the time quotient of the whole process.